The dark proteome of rodent hepatitis E virus: Analysis of intrinsically disordered regions - Zoya Shafat; Anwar Ahmed; Mohammad K Parvez; Asimul Islam; Shama Parveen (Archives of Hepatitis Research - Peertechz Publications, 2022)
Hepatitis E virus (HEV) is the causative agent of Hepatitis E infections across the world. Intrinsically disordered protein regions (IDPRs) or Intrinsically Disordered Protein (IDPs) are regions or proteins that are characterized by a lack of definite structure. These regions or proteins play significant roles in a wide range of biological processes, such as cell cycle regulation, control of signaling pathways, etc. IDPRs or IDPs in proteins are associated with the virus's pathogenicity and infectivity. The occurrence of intrinsic disorder in the proteome of rat HEV remains to be elucidated, which prompted us to explore its dark proteome. In this study, the unstructured/disordered regions of ORF proteins of rat HEV have been examined. We have analyzed the prevalence of intrinsic disorder by using a set of computational predictors. The intrinsic disorder propensity analysis showed that the ORF proteins consisted of a varying fraction of intrinsic disorder. The ORF3 protein was identified with a maximum propensity for intrinsic disorder while the protein ORF6 showed the least propensity for the intrinsic disorder. Further, the analysis revealed ORF6 as highly structured protein (ORDP); ORF1 and ORF4 as moderately disordered proteins (IDPRs); and ORF3 and ORF5 as highly disordered proteins, categorizing them as ordered protein (ORDP), a protein having Intrinsically Disordered Region (IDPR) and Intrinsically Disordered Proteins (IDP) respectively. Such disordered regions may play several important roles in the pathogenesis and replication of viruses. Collectively, this comprehensive study data from our investigation suggested ORF protein's role in the regulation and pathogenesis of rat herpesvirus.